The pains of racism and economic adversity in young Londoners' lives: sketching the contours. Issue 3 (7th February 2023) - Phillips, Coretta
ABSTRACT: This paper sketches an analytical framework to conceptualise the way racial power and socio-economic precarity impacts the everyday lives of young minority ethnic Londoners. Using life stories and photo-elicitation, it elucidates the pains of racialisation, racism, and economic marginalisation using and extending the metrics ( depth, breadth, looseness and tightness ) used in Crewe's (2011. "Depth, Weight, Tightness: Revisiting the Pains of Imprisonment." Punishment and Society 13 (5): 509–529. doi:10.1177/1462474511422172 ) conceptualisation of the contemporary pains of imprisonment. While there is no intention to imply a straightforward parallel between systems of penal power and racial power, the commonalities in the feelings evoked are stark in their affect and effect. This framework offers a means to register the different forms, gradations and intensities of racialising processes which are not easily captured by the singular concept of racism.